SUCCESSFUL TREATMENT OF A CLINICAL CASE OF CONVERSION DISORDER WITH COMBINED ELECTROCONVULSIVE THERAPY AT MILITARY HOSPITAL 175 - Dang Tran Khang; Le Thi Thuy Linh; Nguyen Huu Thien; Nguyen Xuan Trung; Bui Ngoc Cung; Tran Lam (Tạp chí Y học Quân sự, 2026)
Conversion disorder (also known as functional neurological symptom disorder) is classified within the group of somatic symptoms and related disorders. This is a relatively common psychiatric disorder encountered in clinical practice; however, accurate diagnosis and appropriate treatment may be challenging at healthcare facilities lacking specialized psychiatric services. We report the case of a 20-year-old patient whose condition occurred concurrently with a physical illness and had initially been treated under a different diagnostic orientation. The patient was transferred to Military Hospital 175 due to complete paralysis of the right arm and right leg persisting for several months, and was subsequently diagnosed with conversion disorder. The condition did not respond to conventional treatments, including suggestion therapy, antidepressants, antipsychotics, anxiolytics, and physical rehabilitation therapy. The patient was later successfully treated with combined electroconvulsive therapy.